Society, individualism and modernity in Peru - Mejía Navarrete, Julio (2018)
The article analizes the singular character of the constitution of the individualism of popular and cholo origin in contemporary Peru, in order to try to note some possible trends. The antecedents of the cholo individualism from the beginning of last century were based on the Andean culture that facilitated its progress and stopped the social uprooting. The expansion of social individualism as a result of the massive Andean migrations in the sixties, promoted the belief in personal development, the communal legacy in the formation of slums and the diffusion of informality. And in recent decades, individualism has become a hybrid process of neoliberal egocentrism, oligarchical creole vivacity, gamonal-based violence, informality, commodification and utilitarian pragmatism. It seems that the possible developments of individualism and communalism moved in a dynamic of their own that links modernity and andean cultural heritage.